2021
DOI: 10.3390/antibiotics10111424
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Study of the Antibacterial Activity of Basidiomycota Crude Extracts

Abstract: The excessive consumption of antibiotics in clinical, veterinary and agricultural fields has resulted in tremendous flow of antibiotics into the environment. This has led to enormous selective pressures driving the evolution of antimicrobial resistance genes in pathogenic and commensal bacteria. In this context, the World Health Organization (WHO) has promoted research aiming to develop medical features using natural products that are often competitive with synthetic drugs in clinical performance. Fungi are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Bacterial infections still represent a major health problem, amplified by the phenomenon of antibiotic resistance. Micromycetes have long been a reservoir of antibacterial drugs, but higher fungi, i.e., mushroom-forming fungi or macromycetes, are now emerging as a promising source of antimicrobial compounds [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial infections still represent a major health problem, amplified by the phenomenon of antibiotic resistance. Micromycetes have long been a reservoir of antibacterial drugs, but higher fungi, i.e., mushroom-forming fungi or macromycetes, are now emerging as a promising source of antimicrobial compounds [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The metabolites produced by mushrooms and other fungi provide their extracts’ prebiotic and antimicrobial activities, as was observed in Clericuzio et al (2021) [ 35 ]. In this work, metabolites were obtained by extraction using 90% acetone and 10% 2-propanol ( v / v ) from the fruiting bodies of 16 species of Basidiomycetes.…”
Section: Discussionmentioning
confidence: 96%
“…Most of those pathogens are multidrug-resistant and are, therefore, a significant problem for global public health with enormous economic costs. Accordingly, there is an emerging need to find antimicrobials to combat ESKAPE pathogens and minimize their adverse effects [51]. Previously, Garcia et al [21] reported the importance of mushrooms as a source of valuable antibacterial compounds.…”
Section: Antibacterial Activitymentioning
confidence: 99%